The semantic priming project - Hutchison, Keith A.; Balota, David A.; Neely, James H.; Cortese, Michael J.; Cohen-Shikora, Emily R.; Tse, Chi-Shing; Yap, Melvin J.; Bengson, Jesse J.; Niemeyer, Dale; Buchanan, Erin (Behavior research methods, 2013)
Speeded naming and lexical decision data for 1,661 target words following related and unrelated primes were collected from 768 subjects across four different universities. These behavioral measures have been integrated with demographic information for each subject and descriptive characteristics for every item. Subjects also completed portions of the Woodcock–Johnson reading battery, three attentional control tasks, and a circadian rhythm measure. These data are available at a user-friendly Internet-based repository ( http://spp.montana.edu ). This Web site includes a search engine designed to generate lists of prime–target pairs with specific characteristics (e.g., length, frequency, associative strength, latent semantic similarity, priming effect in standardized and raw reaction times). We illustrate the types of questions that can be addressed via the Semantic Priming Project. These data represent the largest behavioral database on semantic priming and are available to researchers to aid in selecting stimuli, testing theories, and reducing potential confounds in their studies.